Thickness, humidity, and polarization dependent ferroelectric switching and conductivity in Mg doped lithium niobate - Neumayer, Sabine M. (2017)
Mg doped lithium niobate (Mg:LN) exhibits several advantages over undoped LN such as resistance to photorefraction, lower coercive fields, and p-type conductivity that is particularly pronounced at domain walls and opens up a range of applications, e.g., in domain wall electronics. Engineering of precise domain patterns necessitates well founded knowledge of switching kinetics, which can differ significantly from that of undoped LN. In this work, the role of humidity and sample composition in polarization reversal has been investigated under application of the same voltage waveform. Control over domain sizes has been achieved by varying the sample thickness and initial polarization as well as atmospheric conditions. In addition, local introduction of proton exchanged phases allows for inhibition of domain nucleation or destabilization, which can be utilized to modify domain patterns. Polarization dependent current flow, attributed to charged domain walls and band bending, demonstrates the rectifying ability of Mg: LN in combination with suitable metal electrodes that allow for further tailoring of conductivity. (C) 2015 AIP Publishing LLC.